The effect of red and white wine on color changes of nanofilled and nanohybrid resin composites - Saijai Tanthanuch; Boonlert Kukiattrakoon; Thanwalee Peerasukprasert; Nilobon Chanmanee; Parnchanok Chaisomboonphun; Apisara Rodklai (Korean Academy of Conservative Dentistry, 2016)
Objectives This study investigated the effect of red and white wine on color changes of nanofilled and nanohybrid resin composite. Materials and Methods Sixty specimens of each resin composite were prepared. Baseline data color values were recorded using a spectrophotometer. Three groups of discs (n = 20) were then alternately immersed in red, white wine, and deionized water (as a control) for twenty five minutes and artificial saliva for five minutes for four cycles. Specimens were then stored in artificial saliva for twenty two hours. This process was repeated for five days following immersion in artificial saliva for two days. Subsequently, the process was repeated again. Data were analyzed by two-way repeated ANOVA, one-way ANOVA, and Tukey's HSD. Results Red wine caused significantly higher color change (ΔE* > 3.3) than did white wine and deionized water (p < 0.05). Nanohybrid resin composites had significantly more color changes than nanofilled resin composite (p < 0.05). Conclusions The effect of red and white wine on the color changes of resin composite restorative materials depended upon the physical and chemical composition of the restorative materials and the types of wine.